Burden of melanoma in China and its provinces from 1990 to 2021: an analysis for the Global Burden of Disease Study 2021 - Yu, Lingling; Yan, Fanshu; Qi, Jinlei; Wang, Lijun; Zhou, Maigeng; Yin, Peng (Frontiers in Public Health, 2024)
BackgroundThe incidence of melanoma in China has been increasing over the past few decades. This study aimed to investigate the burden of melanoma at both national and subnational level in China, where the population is rapidly aging.MethodsThe annual melanoma data from 1990 to 2021 was collected from the Global Burden of Disease (GBD) 2021 China subnational study. Number of cases and age-standardized rates were estimated for incidence, mortality, prevalence, disability-adjusted life-years (DALYs) of melanoma by age and sex at subnational level with 33 province-level administrative units. Joinpoint regression model was used to evaluate the trends in disease burdens attributable to melanoma across time. A decomposition method was used to attribute changes in total deaths and DALYs to three explanatory components: population growth, population aging, and change of age-specific rates.ResultsOver the past 30 years, the age-standardized incidence rate (ASIR) of melanoma in China has shown an upward trend. The ASIR of melanoma in 2021 was 0.7 per 100,000 (95%UI 0.4–0.9), representing an increase of 89.2% (95% UI: 14.7–157.9%) from 1990. Among younger adults aged <60 years, melanoma was more common in men, whereas among older adults who were aged >60 years, it was more common in women. The ASIR was higher in the coastal provinces in 2021 and the age-standardized rates (ASR) of DALYs was generally higher in the western provinces. Total numbers of death and DALYs of melanoma increased over the study period, mainly driven by population aging in China.ConclusionChina has experienced a substantial increase in the burden of melanoma from 1990 to 2021. It is beneficial to develop more targeted strategies for older adults populations, especially for women, to reduce the melanoma burden throughout China, particularly in some coastal and western provinces.